جودة المراجعة في ظل معيار رقابة الجودة الاول - محمد, تواتي; وائل, حساني (University of eloued جامعة الوادي, 2021)
تهدف هذه الدراسة إلى تحليل إلى أي مدى يمكن اعتماد سياسات وإجراءات رقابة الجودة بمكاتب وشركات المراجعة بالجزائر في ظل المعيار الدولي لرقابة الجودة الأول، وهذا من وجهة نظر المجتمع المالي؟، في ظل سياسات وإجراءات مقترحة ومستنبطة أساسا من محتوی المعيار الدولي لرقابة الجودة الأول ( ISQC1 ) ، حيث تم اختبار هذه القابلية من خلال استبيان من وجهة نظر المراجعين الخارجيين وكذلك الفئات المستفيدة من خدماتهم . وخلصت الدراسة إلى وجود قابلية لدى طرفي الدراسة لاعتماد سياسات وإجراءات رقاية جودة المراجعة بالجزائر ، في ظل الإطار المقترح الباحثين ، بالتوافق مع محتوى المعيار الدولي الرقابة الجودة 1 ( ISQC1 ) ، مع الإشارة إلى أن مستويات القبول كانت اعلی لدى المستفيدين من خدمات المراجعة ، منه لدى المراجعين This study aims to analyze to what extent it is possible to adopt policies and procedures for quality control in auditing offices and companies in Algeria in light of the first international standard for quality control, and this is from the point of view of the financial community?, in light of the proposed policies and procedures derived mainly from the content of the first international standard for quality control (ISQC1) ), where this ability was tested through a questionnaire from the point of view of external auditors as well as the groups benefiting from their services. The study concluded that the two parties of the study have the ability to adopt policies and procedures for auditing quality in Algeria, in light of the proposed framework by researchers, in accordance with the content of the international standard for quality control 1 (ISQC1), noting that the levels of acceptance were higher among the beneficiaries of audit services, than among the reviewers
مذكرة ماستر تدقيق محاسبي
Keywords: جودة المراجعة ، معيار رقابة الجودة الأول ، معايير تدقيق الدولية; Audit quality, the first quality control standard, international auditing standards